1997
DOI: 10.1577/1548-8659(1997)126<0428:iomdal>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Macroinvertebrate Drift and Light on the Activity and Movement of Colorado River Cutthroat Trout

Abstract: Most studies of the diel pattern of trout foraging have focused on examining gut fullness at different times of the day. We used radiotelemetry coupled with stomach content and macroinvertebrate drift sampling to compare the diel activity of Colorado River cutthroat trout Oncorhynchus clarki pleuriticus with variation of invertebrate drift and light intensity on six dates during summer 1993 in the North Fork Little Snake River, Wyoming. The percentage of trout active was greater during midday than at night (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 47 publications
8
63
0
Order By: Relevance
“…As in the study by Young et al (1997), the bottom of the net was close to the substratum, and the top extended always above the water surface. Immediately after collection, drift samples were identified to taxonomic genera, and individuals of each genus were counted.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…As in the study by Young et al (1997), the bottom of the net was close to the substratum, and the top extended always above the water surface. Immediately after collection, drift samples were identified to taxonomic genera, and individuals of each genus were counted.…”
Section: Methodssupporting
confidence: 57%
“…To date, a single, pioneer study has investigated the relationships between the drift of invertebrate prey and the foraging activity of salmonids in natural environments (cutthroat trout Oncorhynchus clarki pleuriticus Richardson; Young et al, 1997). However, it provided little insight into interindividual differences, and did not permit an analysis of individual behaviour with respect to fine-scale temporal variations in the abundance of drift in the activity centre of trout.…”
Section: Introductionmentioning
confidence: 99%
“…Even in systems where invertebrates made up only 10-15% of the terrestrial input, they comprised in total more than a third of the diet [36], which seems to be an indication that stream fish often prey selectively on terrestrial invertebrates falling into the water, e.g., [37].…”
Section: Wild Insects For Indirect Consumption By Humansmentioning
confidence: 99%
“…Many studies have documented the feeding periodicity of brook trout in streams. Some of them indicated that salmonids were dayactive (Walsh et al 1988, Young et al 1997 while others considered brook trout as an efficient night predator (Gries et al 1997). Others associate brook trout with a feeding at twilight (Clark and Levy 1988, Sirois and Boisclair 1995, Kreivi et al 1999.…”
Section: Brook Trout Selective Foragingmentioning
confidence: 99%